Botany, Diversity, and Distribution of Black Pepper (Piper nigrum L.) Cultivars in Malaysia - Chen, Chen Yi Shang; Tawan, Cheksum (Borneo Journal of Resource Science and Technology, 2020)
This paper reviewed general botanical description of black pepper (Piper nigrum L.) cultivar by previous botanist, based on uniqueness of Malaysian black pepper cultivars characteristics. Ten important cultivars have been verified i.e. cv. ‘Semongok Aman’, cv. ‘Kuching’, cv. ‘Semongok Emas’, cv. ‘Semongok Perak’, cv. ‘Semongok 1’, cv. ‘Nyerigai’, cv. ‘India’, cv. ‘Lampung Daun Lebar’, cv. ‘Sarikei’, and cv. ‘Yong Petai’. The qualitative and quantitative traits distinctness for each cultivar has been highlighted to assist cultivar identification. Vouchers (dried specimens) for the ten cultivars have also been prepared and deposited at herbarium that located at University Malaysia Sarawak and the duplicates at Malaysian Pepper Board, Kuching. Besides, distribution of each cultivar has also been documented based on information sourced from Malaysian Pepper Board.